Mis-localization of endogenous TDP-43 leads to ALS-like early-stage metabolic dysfunction and progressive motor deficits - Yiying Hu; Alexander Hruscha; Chenchen Pan; Martina Schifferer; Michael K. Schmidt; Brigitte Nuscher; Martin Giera; Sarantos Kostidis; Özge Burhan; Frauke van Bebber; Dieter Edbauer; Thomas Arzberger; et al. (Molecular Neurodegeneration)
Abstract Background The key pathological signature of ALS/ FTLD is the mis-localization of endogenous TDP-43 from the nucleus to the cytoplasm. However, TDP-43 gain of function in the cytoplasm is still poorly understood since TDP-43 animal models recapitulating mis-localization of endogenous TDP-43 from the nucleus to the cytoplasm are missing. Methods CRISPR/Cas9 technology was used to generate a zebrafish line (called CytoTDP), that mis-locates endogenous TDP-43 from the nucleus to the cytoplasm. Phenotypic characterization of motor neurons and the neuromuscular junction was performed by immunostaining, microglia were immunohistochemically localized by whole-mount tissue clearing and muscle ultrastructure was analyzed by scanning electron microscopy. Behavior was investigated by video tracking and quantitative analysis of swimming parameters. RNA sequencing was used to identify mis-regulated pathways with validation by molecular analysis. Results CytoTDP fish have early larval phenotypes resembling clinical features of ALS such as progressive motor defects, neurodegeneration and muscle atrophy. Taking advantage of zebrafish’s embryonic development that solely relys on yolk usage until 5 days post fertilization, we demonstrated that microglia proliferation and activation in the hypothalamus is independent from food intake. By comparing CytoTDP to a previously generated TDP-43 knockout line, transcriptomic analyses revealed that mis-localization of endogenous TDP-43, rather than TDP-43 nuclear loss of function, leads to early onset metabolic dysfunction. Conclusions The new TDP-43 model mimics the ALS/FTLD hallmark of progressive motor dysfunction. Our results suggest that functional deficits of the hypothalamus, the metabolic regulatory center, might be the primary cause of weight loss in ALS patients. Cytoplasmic gain of function of endogenous TDP-43 leads to metabolic dysfunction in vivo that are reminiscent of early ALS clinical non-motor metabolic alterations. Thus, the CytoTDP zebrafish model offers a unique opportunity to identify mis-regulated targets for therapeutic intervention early in disease progression.